The Effects of Progressive Resistance Exercise on Recovery Rate of Bone and Muscle in a Rodent Model of Hindlimb Suspension - Song, Hansol; Cho, Suhan; Lee, Ho-Young; Lee, Hojun; Song, Wook (Frontiers in Physiology, 2018)
Purpose: This study aimed to examine the exercise-mediated musculoskeletal recovery following hindlimb suspension in order to identify whether bone modeling and muscle hypertrophy would eventuate in a synchronized manner during recovery stage. Methods: To identify whether 2-week hindlimb suspension would be sufficient to induce a significant reduction of physiological indices in both tibia and adjacent hindlimb muscles, a total of 20 rats was randomized into 2-week hindlimb suspension (n=10, HS) and age-matched control group (n=10, CON). Another batch of rats were randomly assigned to three different groups to identify recovery intervention effects following suspension: (1) 2-week hindlimb suspension followed by 4 week-spontaneous reloading recovery (HRE, n=7). (2) 2-week hindlimb suspension followed by 4 week-progressive resistance ladder climbing exercise (HEX, n=7). (3) Age-matched control (CON, n=7). DXA, micro-CT, and 18F-sodium fluoride (NaF) imaging, and EIA analysis were utilized to measure tibia bone indices. Hindlimb muscle wet weight and grip strength were measured to evaluate muscle mass and strength respectively. Results: In study 1, bone quality values (BV/TV: - 27%, aBMD: -23%, mineral contents: -7.9%, mineral density: -4.1%, and bone density: -38.9%) and skeletal muscle weight (soleus: -46.8%, gastrocnemius: -19.6%, plantaris: -20.8%, TA: -22.8%, EDL: -9.9%) were significantly lower in HS group compared to CON group. In study 2, Micro-CT and DXA-based bone morphology (Bone density, BT/TV, and aBMD) were fully recovered in HRE or HEX group. However, suspension-induced dysregulation of bone mineral metabolism was returned to age-matched control group in only HEX group, but not in HRE group. A greater level of biomarkers of bone formation (P1NF) and resorption (CTX-1) was observed in only HRE group compared to CON. The hindlimb skeletal muscle mass was significantly lower in both HRE and HEX groups compared to CON group. Hindlimb grip strength was the greatest in HEX group, followed by CON and HRE groups. Conclusion: Following hindlimb suspension, progressive resistance exercise promotes recovery rates of bone and skeletal muscle strength without a significant increase in muscular mass, suggesting that exercise-induced reacquisition of bone and muscle strength is independent of muscle hypertrophy during early recovery stage.